SAXS study of crotapotin at low pH - Abrego, José Ramon Beltran [UNESP]; Craievich, Aldo Felix; Mascarenhas, Yvonne Primerano; Laure, Carlos J. (Biophysical Society, 1993)
The structure of crotapotin, a protein extracted from the venom of the Crotalus durissus terrificus, in solution at pH = 1.5, was studied by SAXS. The experimental results yield structural parameter values of the molecular radius of gyration R(g) = 13.6 angstrom, volume v = 16.2 x 10(3) angstrom3 and maximal dimension D(max) = 46 angstrom. The distance distribution function deduced from the scattering measurements is consistent with an overall molecular shape of an oblate ellipsoid of revolution with assymetry parameter nu = 0.45.